Assessment of the impulse noise attenuation by earplugs in metalworking processes - Rafał Młyński; Emil Kozłowski (Nofer Institute of Occupational Medicine, 2014)
Background: The aim of the study was to answer the question of whether earplugs provide sufficient protection in the exposure to impulse noise generated during metalworking processes. Material and Methods: The noise generated by die forging hammer and punching machine was characterized. Using an acoustic test fixture, noise parameters (LCpeak, LAmax) under 24 earplugs, foam, winged and no-roll, were measured. Octave band method was used to calculate values of LAeq under earplugs. Results: It was found that in the case of punching machine the exposure limit value of A-weighted noise exposure level, normalized to an 8-h working day (LEX,8h = 94.8 dB) of noise present at the workstation, was exceeded, while in the case of die forging hammer both the exposure limit value of this parameter (LEX,8h = 108.3 dB) and the exposure limit value of peak sound pressure level (LCpeak = 148.9 dB) were exceeded. The assessment of noise parameters (LCpeak, LAmax, LAeq) under earplugs revealed that the noise attenuation can be insufficient, sufficient, or too high. Conclusions: Earplugs can be suitable hearing protection devices in metalworking processes. Of the 24 earplugs included in this study, 9 provided appropriate noise attenuation in the case of tested die forging hammer and 10 in the case of tested punching machine. Med Pr 2014;65(2):197-207